A polarized reflectance model for remote sensing of densely vegetated surfaces. Issue 3 (1st September 2020) - Zhao, Haimeng; Yang, Bin; Wang, Qiang; Wu, Yi; Sun, Shanlin
ABSTRACT: In this paper, we propose a modified model which takes the variation of leaf orientation in zenithal space into consideration. It is special because of the linkage between the parameterization of leaf inclination angle and polarized reflectance modelling. The modified model is compared to the Rondeaux-Herman model, the Nadal-Bréon model and a one-parametric linear model using remotely sensed polarized data which was obtained by the Research Scanning Polarimeter (RSP) over Oklahoma on 16 September 2005. The comparison suggests the modified model accurately captures the polarized reflectance of dense vegetation and works more precisely than the other models.